An investigation of the practices employed by an environmental community-based organization to successfully sustain its school based and community based projects (A case study) - Hlophe, Nomalanga Nokuthula (Rhodes University, Faculty of Education, Department of Education, 2016)
Community-based organizations (CBOs) play a crucial role in sustainable development and hence it is important that they are promoted, guided and supported by state agencies and the private sector. The South African government encourages communities to establish co-operatives as a tool or strategy to address local social issues and risks and act accordingly. The purpose of this case study was to determine what aspects of the establishment and operation of a successful community-based environmental organization are producing sustained school and community projects. The study set out to investigate and audit the activities of a successful environmental CBO so as to determine how it has successfully sustained its school and community environmental projects. The reason for this investigation was to inform other CBOs and the state environmental agencies that support them on how to sustain their environmental activities in community and school contexts. The investigation was designed as an interpretive case study, which used document analysis, semi-structured interviews and observations to gather data. The gathered data was analyzed through inductive analysis to interpret and audit reported activities. Analytical memos were used to represent key themes in relation to the successful operations of the organization. Through auditing and reporting the activities in the analytical memos, analytical statements were developed. Those statements guided the discussion and informed the study"Ÿs findings and recommendations. After investigating this CBO, it was concluded that, their success is a result of the establishment of a networking forum with different stakeholders and parties, community involvement in different projects, partnerships with local schools to develop and expand their curriculum practice, CBO networking locally and internationally and finally, their participation in annual and continuous environmental competitions/projects/programs. The insights gained and lessons learned will be used to advice and support community based co-operatives in environmental learning activities in school and community contexts as part of my ongoing work.
Keywords: Uncatalogued